Organizational culture, corporate social responsibility and financial performance of companies in Jordan and Palestine - Hussein Ali, Hosni Shareif Hussein (2018)
A review of the literature shows the necessity of corporate social responsibility (CSR), due to its effect on corporate financial performance (CFP). Although this relationship has been investigated, there are still inconsistent results in the previous studies, especially, in the successful adoption of CSR in companies, and the relationship between organizational culture and CFP. There is also a lack of formalized models regarding the impact of CSR activities on the relationship between organizational culture and CFP, especially in the context of developing countries, such as, Jordan and Palestine. This study aims to achieve the following research objectives via the resource based view and the stakeholder theory. (1) To examine the impact of CSR activities on CFP. (2) To examine the impact of organizational culture on CFP. (3) To examine the impact of organizational culture on CSR. (4) To examine the mediating role of CSR activities between organizational culture and CFP. In order to achieve the study’s objectives, this study used a quantitative approach. The data was collected from 398 managers in listed companies in Jordan and Palestine using questionnaires. In addition to that, the present study uses the structural equation modeling through partial least squares method. Based on the results, it is found that there are significant relationships between a) CSR and CFP, b) organizational culture and CFP, and c) organizational culture and CSR. This study also contends that CSR activities mediate the relationship between organizational culture and CFP. The present study analyzed the data of each country separately. The results revealed that the relationship between CSR and CFP in Jordan is significant, but not in Palestine. This study also confirms that CSR activity is a mediator in the relationship between organizational culture and CFP in Jordan, but not a significant mediator in Palestine. Theoretically, the proposed framework of the study provided important contributions to the literature of CSR activities as mediator in the relationship between organizational culture and CFP. This study also provides a useful model to better understand the relationship between CSR and CFP to advocate companies to practice CSR and obtain better financial performance. The results of the current study could benefit the policy-makers in both countries. The government of both countries should strengthen the policies on CSR to enhance the performance of these companies, particularly the listed companies.